APPLICATION OF THE RIBH CONCEPT IN CV. HIELMY CRAFTINDO BAKTI, SUKARUAS VILLAGE, RAJAPOLAH DISTRICT, TASIKMALAYA REGENCY - Mira Nurmayanti (Syari'ah Economics, 2022)
This study aims to analyze the concept of ribh and analyze the application of the concept of ribh by CV. Hielmy Craftindo Bakti. This research uses a qualitative descriptive method. The research data sources consist of primary data and secondary data. Primary data obtained from observations and interviews with company owners. Secondary data were obtained from a number of books, articles, and journals related to this research. The results show that the concept of ribh is a trade concept applied by the Prophet Muhammad. The trade concept of the prophet Muhammad is called "goodness trade" (dagang kahadean, Sundanese) which means the process of buying and selling goodness, namely the buying and selling process that uses the concept of Islamic law. The concept of ribh applied by CV. Hielmy Craftindo Bakti does not use the practice of debt and credit, because it will make both parties miserable.